A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae) - Rabeling, Christian; Cover, Stefan P.; Johnson, Robert A.; Mueller, Ulrich G. (Zootaxa, 2007)
We revise and key Trachymyrmex ants occurring in North America north of Mexico. We recognize nine species, including one new species from southern Arizona: T. arizonensis (Wheeler), T. carinatus Mackay & Mackay, T. desertorum (Wheeler), T. jamaicensis (André), T. nogalensis Byars, T. pomonae Rabeling & Cover sp. nov., T. septentrionalis (McCook), T. smithi Buren, and T. turrifex (Wheeler). Two infraspecific taxa are synonymized: T. smithi neomexicanus Cole syn. nov. (= T. smithi) and T. turrifex caroli Wheeler syn. nov. (= T. turrifex). We briefly characterize the previously undescribed queens of T. desertorum and T. nogalensis, and the males of T. desertorum and T. turrifex. We include keys for the identification of workers, queens and males, along with distribution maps for all species. A phylogenetic analysis of DNA sequence information for parts of the mitochondrial gene Cytochrome Oxidase I and the first intron of the F1copy of the nuclear protein-coding gene Elongation Factor 1-α is used to characterize the intraversus inter-specific genetic variation of several populations per species. The molecular phylogenetic analysis supports our taxonomic conclusions concerning the North American Trachymyrmex species.